28.4k views
3 votes
Please help, thank you

Please help, thank you-example-1

1 Answer

2 votes

Answer:


\displaystyle x=(-8\pm√((8)^2-4(4)(-221)))/(2(4))\ \text{; x = 6.5 and x = -8.5}

Explanation:

Subtract the right side of the given equation to put it into standard form:

4x² +8x -221 = 0

Then the coefficients used in the quadratic formula are ...

  • a = 4
  • b = 8
  • c = -221

When these are filled into the form ...


\displaystyle x=(-b\pm√(b^2-4ac))/(2a)

the result is as shown above.

User Samich
by
5.7k points